Catholic identity of Congregatio Immaculati Cordis Mariae (CICM) schools in the Philippines : input to a CICM-catholic inspired formation plan - Dilim, Abraham F. (Saint Louis College, City of San Fernando, La Union : [s.n.], 2018)
This study aim to assess the extent of manifestation of the Catholic Identity of the five Congregation of the Immaculate Heart of Mary (Congregatio Immaculati Cordis Mariae, CICM) schools in the Philippines along the five key characteristics of a Chatolic School. It also looked into the strengths and weaknesses along forty (40) indicators of the five (5) key areas of assessment on the Catholic Identity of CICM Schools in the Philippines. The results became bases in the crafting of a CICM-Catholic Inspired Formation Plan for CICM schools in the Philippines. The descriptive-research design was used in this study. There were 1037 respondents from the five CICM schools in the Philippines. 46 hold managerial positions, 348 employees, and 643 students. questionnaire was used to gather data which were treated using frequencies and weighted means. This study found that the Catholic identity of CICM schools along the live key characteristics of a Catholic school is manifested, however, it was discovered that CICM schools can still do better. From the five key characteristics of a Catholic School, "Religious Education" posted the highest manifestation. Among the 40 indicators, nine (9) were evaluated as strengths, and 31 were weaknesses. A validated CICM-Catholic Inspired Formation Plan was crafted to sustain the strengths and address the weaknesses of CICM schools in the Philippines.
Bibliography: pages 156-164.
CHED-La Union
Keywords: Religious education